Variability of the evolutionary PCR results in patients with COVID -19 - Ernesto Sánchez Hernández; Odalis Cardona Gordo; Jacno Erik Ferrer Castro; Fernando Pérez Fouces; Adrial Despaigne Bicet (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The new coronavirus specimen (COVID-19), has generated scenarios of sanitary emergencies in many countries from all continents. Objective: To characterize the variability of the PCR evolutionary results in patients with COVID-19. Methods: An observational, descriptive, prospective and cross-sectional study was carried out in 68 patients with COVID-19 (children and adults from both sexes) admitted in Dr. Joaquín Castillo Duany Military Hospital in Santiago de Cuba, from March 12th to April 30th, 2020. To collect the virological, the nasal and pharyngeal use of isotope was carried out, which analysis of PCR-RT was processed in the territorial reference center.  Management, social, demographic and epidemiological variables were included, among others. Results: Female sex prevailed in the series (52.9 %). Two PCR-RT fast tests were made to all the patients, through their clinical course, 40.0 % of the children and 10.0 % of the aged patients requiered a third virological test.  In the second and third third of the clinical and epidemiological observation period, the report of the result averaged 1.5 days (SD ± 0.6) and 3.2 days (SD±1.6), respectively.  After 15 days of treatment there were active positive cases    in all populational groups; likewise 60.0 % of those with viral charge between 16-20 days were asymptomatic, as the 66.7 % of those with more than 20 days under medication. Conclusions: Independently from the age and duration of the medical treatment, some patients remained with detectable viral charge. It is not adviced to discharge patients without a negative PCR-RT, above all for asympthomatic cases, in whom the evolutionary clinical course has been less favorable.